Slicing heterogeneous solid using octree-based subdivision and trivariate T-splines for additive manufacturing. Issue 1 (6th January 2020) - Li, Bin; Fu, Jianzhong; Zhang, Yongjie Jessica; Lin, Weiyi; Feng, Jiawei; Shang, Ce
Abstract : Purpose: Majority of the existing direct slicing methods have generated precise slicing contours from different surface representations, they do not carry any interior information. Whereas, heterogeneous solids are highly preferable for designing and manufacturing sophisticated models. To directly slice heterogeneous solids for additive manufacturing (AM), this study aims to present an algorithm using octree-based subdivision and trivariate T-splines. Design/methodology/approach: This paper presents a direct slicing algorithm for heterogeneous solids using T-splines, which can be applied to AM based on the fused deposition modeling (FDM) technology. First, trivariate T-splines are constructed using a harmonic field with the gradient direction aligning with the slicing direction. An octree-based subdivision algorithm is then used to directly generate the sliced layers with heterogeneous materials. For FDM-based AM applications, the heterogeneous materials of each sliced layer are discretized into a finite number of partitions. Finally, boundary contours of each separated partition are extracted and paired according to the rules of CuraEngine to generate the scan path for FDM machines equipped with multi-nozzles. Findings: The experimental results demonstrate that the proposed algorithm is effective and reliable, especially for solid objects with multiple materials, which could maintain the model integrity throughout the process from the original representation to the final product in AM. Originality/value: Directly slicing heterogeneous solid using trivariate T-splines will be a powerful supplement to current technologies in AM.